2009
DOI: 10.1093/nar/gkp643
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of homology-directed gene targeting at an endogenous human locus by a nicking endonuclease

Abstract: Homologous recombination (HR) is a highly accurate mechanism of DNA repair that can be exploited for homology-directed gene targeting. Since in most cell types HR occurs very infrequently (∼10−6 to 10−8), its practical application has been largely restricted to specific experimental systems that allow selection of the few cells that become genetically modified. HR-mediated gene targeting has nonetheless revolutionized genetics by greatly facilitating the analysis of mammalian gene function. Recent studies show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 51 publications
4
47
0
Order By: Relevance
“…It has been shown that DNA-nicking enzymes allow homology-directed gene targeting in mammalian cells (Lee et al 2004;van Nierop et al 2009) and that nickases can be created by engineering naturally occurring restriction enzymes (Sanders et al 2009) or meganucleases (McConnell Smith et al 2009). However, these enzymes are not readily reprogrammed to target any predetermined DNA sequence and thus cannot be used to modify DNA sequences at user-defined genomic sites.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that DNA-nicking enzymes allow homology-directed gene targeting in mammalian cells (Lee et al 2004;van Nierop et al 2009) and that nickases can be created by engineering naturally occurring restriction enzymes (Sanders et al 2009) or meganucleases (McConnell Smith et al 2009). However, these enzymes are not readily reprogrammed to target any predetermined DNA sequence and thus cannot be used to modify DNA sequences at user-defined genomic sites.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was demonstrated that mammalian cells can efficiently utilize HDR to repair single-strand DNA gaps opposite an abasic site or benzo[a]pyrene adduct (Adar et al 2009). DNA nicks generated by adeno-associated virus (AAV) Rep78 and Rep68 proteins can greatly enhance HDR (van Nierop et al 2009). Furthermore, a ''nick-only'' version of the I-Anil homing endonuclease was also shown to stimulate HDR-mediated DNA repair in mammalian cells using a reporter assay system engineered to contain the I-Anil target site (Smith et al 2009;Metzger et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Next, the cells were subjected to green fluorescent protein (GFP)-based fluorescence-activated single-cell sorting and clonally expanded as detailed elsewhere (16). …”
Section: Methodsmentioning
confidence: 99%